A method for preparing super-hydrophobic optical film applicable to different wavelengths
By constructing a micro-nano structure with different refractive indices on the surface of the optical film, the problem of high reflectivity of the existing optical film under different wavelength conditions is solved, and the influence of moisture on optical performance is reduced through the superhydrophobic effect, achieving the effects of low reflectivity and high transmittance.
Patent Information
- Application Number
- CN202411805088.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing optical films have high reflectivity under different wavelength conditions and are prone to deterioration of optical properties due to moisture, affecting the transmission and reflection effects.
A method including surface cleaning, grinding, silicon oxide film deposition, metal copper melt deposition and nanodry etching is adopted to construct micro-nano structures with different refractive indices to improve hydrophobicity and reduce reflectivity.
The low reflectivity and high transmittance of the optical film under different wavelength conditions are achieved, and the influence of moisture on optical performance is reduced due to the superhydrophobic effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical films, and more specifically, to a method for preparing a super-hydrophobic optical film that can be applied to different wavelengths. Background Art
[0002] Optical film is an optical medium material that transmits light beams through interfaces. It is widely used in the fields of optics and optoelectronics to prepare various optical instruments. Among them, anti-reflection film is gradually gaining attention.
[0003] In lasers, anti-reflection films can reduce the loss of components within the cavity; in lidar, anti-reflection films can improve signal stability; in display screens, anti-reflection films can reduce the glare of ambient light; in photovoltaic cells, anti-reflection films can increase the intensity of light reaching the active layer.
[0004] In the prior art, a single layer or a multilayer (AR-ML) coating is added to the glass surface, and the stacking effect of different refractive indices of the coating is utilized to cause destructive interference of multiple wavefronts reflected on each interface, thereby reducing the reflectivity of the surface. However, due to the resonant nature of interference, the response to wavelength and incident angle is often narrowband. If different thicknesses or gradient refractive index ML structures are used, the AR bandwidth can be expanded, but at the expense of the achievable minimum reflectivity, thereby ensuring that the optical film has a high transmission effect. In addition, the surface of the optical film is prone to the problem of reduced optical performance due to moisture. After the surface of the optical film absorbs moisture, water mist or water droplets are formed, which affects the transmission and reflection of light, and is prone to image blur and distortion.
[0005] Therefore, how to prepare a new optical film so that it has a lower reflection effect under different wavelength conditions, ensures the transmittance of the optical film, and has a good hydrophobic effect on the surface of the optical film to further reduce the influence of moisture on the transmittance of the optical film is a problem to be solved. Summary of the invention
[0006] In order to prepare a new optical film so that it has a lower reflection effect under different wavelength conditions, ensure the transmittance of the optical film, and the surface of the optical film has a good hydrophobic effect, further reducing the influence of moisture on the transmittance of the optical film, the present application provides a method for preparing a super hydrophobic optical film that can be applied to different wavelengths.
[0007] The present application provides a method for preparing a super-hydrophobic optical film that can be applied to different wavelengths, using the following technical solution:
[0008] A method for preparing a super-hydrophobic optical film applicable to different wavelengths comprises the following steps:
[0009] S1, cleaning the surface of the glass substrate, polishing the surface, cleaning the surface, and then sputtering and depositing a silicon oxide film to obtain a deposited glass;
[0010] S2. Melting and depositing metal copper on the surface of the deposition glass, followed by annealing and nickel gun purging to obtain a semi-finished product; and finally performing nano dry etching to obtain a finished product.
[0011] By adopting the above technical solution, the surface of the glass substrate is cleaned and then polished to increase the surface roughness, which is convenient for loading the deposited silicon oxide, ensuring the adhesion stability of the silicon oxide, and improving the dispersion effect of the micro-nano structure on the surface of the deposited glass. The silicon oxide layer has a good hydrophobic effect, and the micro-nano structure can increase the contact angle, thereby further improving the hydrophobic effect. Combined with the high transmittance and low reflectivity of the micro-nano structure to light, it is ensured that the optical film can still have the advantage of low reflectivity under different wavelength conditions.
[0012] After the surface of the deposited glass is subjected to melt deposition of metallic copper, a multilayer anti-reflection film structure of nano-scale copper film and silicon oxide film is used to further improve the transmittance of the optical film and reduce the reflectivity. The nanostructure construction of nano-dry etching can further reduce the light reflectivity. The attachment of the copper film and the treatment of nano-dry etching can further construct the rough morphology of the surface nanostructure, increase the contact angle with water droplets, and further improve the hydrophobic effect, so that the optical film still has the advantage of low light reflectivity under different wavelength conditions and has a super hydrophobic effect.
[0013] Preferably, the specific steps of cleaning in S1 are as follows:
[0014] The glass substrate is ultrasonically cleaned by using one or more of acetone, ethanol and deionized water, and then cleaned by oxygen plasma.
[0015] By adopting the above technical solution, acetone, ethanol or deionized water is used to clean the surface of the glass substrate to remove dirt and impurities. In combination with oxygen plasma cleaning, high-energy ions can be used to bombard pollutant molecules, making it easier for pollutants to separate from the surface of the glass substrate. Oxygen will form active oxygen species in the plasma. These species have strong oxidizing ability and can react with organic pollutants on the glass surface to further remove pollutants, improve the clarity of the glass substrate surface, and facilitate the deposition of silicon oxide film on the glass substrate surface, thereby improving the adhesion stability of the silicon oxide film layer on the glass substrate surface. The anti-reflection effect of the silicon oxide film layer is combined with a good hydrophobic effect to improve the transmittance and hydrophobicity of the optical film.
[0016] Preferably, the surface grinding is performed by rubbing the surface with wurtzite boron nitride particles for 30-60 seconds, and the wurtzite boron nitride particles are prepared from wurtzite boron nitride and polycarbonate liquid in a mass ratio of 1:0.2-0.4.
[0017] By adopting the above technical scheme, wurtzite boron nitride particles are flat-ground on the surface of a glass substrate. The hexagonal crystal structure of the wurtzite boron nitride particles is utilized, and combined with its relatively high hardness, during the flat-ground process, the hexagonal wurtzite boron nitride can utilize the raised edges on the outer surface to produce nano-scale scratches on the surface of the glass substrate. Combined with the high toughness effect of the polycarbonate liquid, the nano-scale scratches are ensured to have an intermittent structure, and long, excessively large scratches are not likely to appear. The depth of scratches on the surface of the glass substrate during the flat-ground process is ensured to be at the nano-level, and is not likely to be too deep while increasing the roughness. The deposition stability of silicon oxide is improved, and the nano-scale structure is ensured to exist after the silicon oxide is deposited. Through the dense nano-scale structure, the reflection phenomenon caused by the sharp change in the refractive index of incident light of different wavelengths is reduced, thereby reducing the reflectivity of the optical film.
[0018] Preferably, the specific steps of sputtering and depositing the silicon oxide film are as follows:
[0019] Using 99.99% pure silicon dioxide, at a base pressure of 1.58×10 -1 Pa-1.63×10 -1 Pa, temperature 24-27°C, pure argon, argon flow rate 42sccm-44sccm, the ratio of argon to oxygen is 1:1.12-1.18.
[0020] By adopting the above technical solution, high-purity silicon dioxide is deposited to form a silicon oxide film layer with anti-reflection and super-hydrophobic effects, and the bottom pressure, temperature and argon gas flow rate are limited to ensure the uniformity of silicon oxide deposition, so that the optical film has low reflection and super-hydrophobic effects under conditions of incident light of different wavelengths.
[0021] Preferably, the specific steps of the S2 metal copper melt deposition are as follows:
[0022] Copper, rare earth lanthanum and antimony oxide with a purity of 99.99% are mixed evenly, and the raw material ratio of copper, rare earth lanthanum and antimony oxide is 1:0.005-0.01:0.01-0.015. Under argon protection, they are heated to 1100-1200°C until they are melted, and then sprayed onto the surface of the deposition glass under argon protection.
[0023] By adopting the above technical scheme, the melting points of copper, rare earth lanthanum and antimony oxide are all less than 1100°C to ensure the melting effect. After being evenly sprayed onto the surface of the deposited glass, nano-copper is first used to scatter the incident light to break the reflection particle size of the incident light, and then the light absorption effect of rare earth lanthanum is used to further reduce the reflectivity. Finally, the anti-reflection effect of the high transmittance of antimony oxide is combined to further improve the transmittance of the optical film and reduce the reflectivity.
[0024] Preferably, the thickness of the deposited film of copper, rare earth lanthanum and antimony oxide is 4-6 nm.
[0025] By adopting the above technical solution, the thickness of the deposited film layer is limited, ensuring high transmittance while having a good anti-reflection effect.
[0026] Preferably, the specific steps of the S2 annealing treatment are as follows:
[0027] First, the temperature is lowered to 660-690°C at a cooling rate of 2-3°C / min, then to 510-550°C at a cooling rate of 3-5°C / min, and finally to 200-250°C at a cooling rate of 5-10°C / min.
[0028] By adopting the above technical scheme, firstly, annealing is performed at a relatively slow speed to 660-690°C. The melting point of antimony oxide is about 650°C, so it is still in a hot melt state. During the annealing process, copper and rare earth lanthanum are first deposited and attached, and the viscosity and fluidity of hot melt antimony oxide are used to pull copper and rare earth lanthanum, prevent copper and rare earth lanthanum from agglomerating, shrinking and deforming, and affect the uniformity of the nano film layer. The highly uniform nano film layer can further reduce the reflectivity of light of different wavelengths; then the cooling rate is increased to cool to 510-550°C to further stabilize the uniform distribution of the nano film layer, and finally the temperature is reduced to 200-250°C at a high rate to control the density and size of the nano particles. While ensuring the uniformity, dry etching treatment is combined to form a uniformly distributed nano array structure on the surface of the optical film, thereby reducing the reflectivity and improving the transmittance.
[0029] Preferably, the nickel gun is purged for 10-20 minutes.
[0030] By adopting the above technical solution, the purging time of the nickel gun is limited, tiny dust particles and pollutants on the surface are removed, the surface cleanliness of the optical film is ensured, and the formation of a uniformly distributed nanoscale array structure during the nano dry etching process is facilitated, thereby improving the transmittance of the optical film under conditions of incident light of different wavelengths and reducing the reflectivity.
[0031] Preferably, the nano dry etching is performed using nano silicon dioxide particles as a mask.
[0032] Preferably, the average etching depth of the semi-finished product surface is 3-4 nm.
[0033] By adopting the above technical solution and using nano-silica particles as a mask, the dispersion of silica particles can help achieve a more uniform etching effect. The dynamic movement and redistribution of particles during the etching process can help reduce the uneven etching phenomenon. By constructing a uniformly distributed nano-column structure and limiting the etching depth of the surface, the reflectivity of the optical film can be reduced and the transmission effect can be improved.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. Silicon oxide film and copper film are deposited on the surface of the glass substrate. By introducing micro-nano structures with different refractive indices on the surface of the optical film, a refractive index gradient layer can be formed to further reduce the reflection of light at the interface; and nano dry etching is performed to further adjust the distribution of the nano-scale structure. For incident light of different wavelengths, the micro-nano structure can reduce the reflection phenomenon caused by the sharp change of the refractive index, so that the incident light of different wavelengths has the advantage of low reflectivity; at the same time, the silicon oxide film, copper film and micro-nano structure can increase the contact angle, thereby improving the super hydrophobic effect.
[0036] 2. The wurtzite boron nitride particles are ground on the surface of the glass substrate. During the grinding process, the hexagonal wurtzite boron nitride can use the raised edges on the outer surface to produce nano-scale scratches on the surface of the glass substrate. Combined with the high toughness effect of the polycarbonate liquid, the nano-scale scratches are intermittent in structure, and long and large scratches are not easy to appear. The depth of the scratches on the surface of the glass substrate during the grinding process is guaranteed to be at the nanometer level. Through the dense nano-scale structure, the reflection phenomenon caused by the sharp change of the refractive index of incident light of different wavelengths is reduced, thereby reducing the reflectivity of the optical film.
[0037] 3. The melting points of copper, rare earth lanthanum and antimony oxide are all less than 1100°C. To ensure the melting effect, after being evenly sprayed onto the surface of the deposited glass, nano-copper is first used to scatter the incident light and break the reflection particle size of the incident light. Then, the light absorption effect of rare earth lanthanum is used to further reduce the reflectivity. Finally, the anti-reflection effect of high transmittance of antimony oxide is combined to further improve the transmittance of the optical film and reduce the reflectivity. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments.
[0039] Preparation Example of Wurtzite Boron Nitride Particles
[0040] Preparation Example 1: Wurtzite boron nitride particles are prepared by the following method:
[0041] The polycarbonate liquid is heated to 240° C. and completely melted to obtain the polycarbonate liquid; the average particle size of the wurtzite boron nitride is 3 μm, and the wurtzite boron nitride has a hexagonal crystal structure;
[0042] 0.3 kg of polycarbonate liquid is evenly sprayed on the surface of 1 kg of wurtzite boron nitride, and the wurtzite boron nitride is dried and dispersed until the wurtzite boron nitride does not stick to each other and agglomerate to obtain finished wurtzite boron nitride particles.
[0043] Preparation Example 2: This preparation example differs from Preparation Example 1 in that:
[0044] 0.2 kg of polycarbonate liquid is evenly sprayed on the surface of 1 kg of wurtzite boron nitride, and the wurtzite boron nitride is dried and dispersed until the wurtzite boron nitride does not stick to each other and agglomerate to obtain finished wurtzite boron nitride particles.
[0045] Preparation Example 3: This preparation example differs from Preparation Example 1 in that:
[0046] 0.4 kg of polycarbonate liquid is evenly sprayed on the surface of 1 kg of wurtzite boron nitride, and the wurtzite boron nitride is dried and dispersed until the wurtzite boron nitride does not stick to each other and agglomerate to obtain finished wurtzite boron nitride particles. Example
[0047] Example 1: A method for preparing a super-hydrophobic optical film applicable to different wavelengths:
[0048] S1. The surface of the glass substrate was ultrasonically cleaned with ethanol at 20kHz for 10 minutes, and then ultrasonically cleaned with deionized water for 5 minutes. After the surface of the glass substrate was air-dried, it was placed in a plasma cleaner and continued to be cleaned for 10 minutes using oxygen to generate plasma. After cleaning, the surface was air-dried. The surface was air-dried. The wurtzite boron nitride particles prepared in Preparation Example 1 were spread on the surface of the glass substrate. 20g of wurtzite boron nitride particles were dispersed per square meter of the glass substrate surface. The surface of the wurtzite boron nitride particles was loaded with a steel plate and rubbed flat for 30s under a pressure of 2kg. Then, the wurtzite boron nitride particles on the surface of the glass substrate were removed by water spraying. After the surface was cleaned, the surface was dried. Then, silicon dioxide with a purity of 99.99% was used at a bottom pressure of 1.62×10 -1 sputtering and depositing a silicon oxide film under the conditions of 1:1.15, 25°C, pure argon, 43 sccm argon flow rate, and a ratio of argon to oxygen of 1:1.15, wherein the average thickness of the silicon oxide film is 10 nm, to obtain a deposited glass;
[0049] S2. Take 1kg of copper, 0.008kg of rare earth lanthanum and 0.0122kg of antimony oxide and mix them evenly. The purity of copper, rare earth lanthanum and antimony oxide is 99.99%. Under argon protection, heat them to 1150°C and melt them completely. Then, under argon protection, spray them evenly onto the surface of the deposition glass. Then, anneal them. First, cool them to 680°C at a cooling rate of 2°C / min, then cool them to 520°C at a cooling rate of 4°C / min, and finally cool them to 200°C at a cooling rate of 8°C / min. The average thickness of the deposited film layer of copper, rare earth lanthanum and antimony oxide is 5nm. Purge with a nickel gun for 10min to obtain a semi-finished product. The semi-finished product is etched using nano-silicon dioxide particles as a mask. The average particle size of the nano-silicon dioxide particles is 40nm. The average etching depth of nano dry etching is 3nm to obtain a finished product.
[0050] Embodiment 2: This embodiment differs from Embodiment 1 in that:
[0051] S1. The surface of the glass substrate was ultrasonically cleaned with ethanol at 20kHz for 10 minutes, and then ultrasonically cleaned with deionized water for 5 minutes. After the surface of the glass substrate was air-dried, it was placed in a plasma cleaner and continued to be cleaned for 10 minutes using oxygen to generate plasma. After cleaning, the surface was air-dried. The surface was air-dried. The wurtzite boron nitride particles of Preparation Example 2 were spread on the surface of the glass substrate. 20g of wurtzite boron nitride particles were dispersed per square meter of the glass substrate surface. The surface of the wurtzite boron nitride particles was loaded with a steel plate and rubbed flat for 30s under a pressure of 2kg. Then, the wurtzite boron nitride particles on the surface of the glass substrate were removed by water spraying. After the surface was cleaned, the surface was dried. Then, silicon dioxide with a purity of 99.99% was used at a bottom pressure of 1.58×10 -1 sputtering and depositing a silicon oxide film under the conditions of 1:1.12, 27°C, pure argon, 42 sccm argon flow rate, and a ratio of argon to oxygen of 1:1.12, wherein the average thickness of the silicon oxide film is 10 nm, to obtain a deposited glass;
[0052] S2. Take 1kg of copper, 0.005kg of rare earth lanthanum and 0.01kg of antimony oxide and mix them evenly. The purity of copper, rare earth lanthanum and antimony oxide is 99.99%. Under argon protection, heat them to 1100℃ and melt them completely. Then, under argon protection, spray them evenly onto the surface of the deposition glass. Then, anneal them. First, cool them to 660℃ at a cooling rate of 2℃ / min, then cool them to 510℃ at a cooling rate of 3℃ / min, and finally cool them to 200℃ at a cooling rate of 5℃ / min. The average thickness of the deposited film layer of copper, rare earth lanthanum and antimony oxide is 4nm. Purge with a nickel gun for 10min to obtain a semi-finished product. The semi-finished product is etched using nano-silicon dioxide particles as a mask. The average particle size of the nano-silicon dioxide particles is 40nm. The average etching depth of nano dry etching is 3nm to obtain a finished product.
[0053] Embodiment 3: This embodiment differs from Embodiment 1 in that:
[0054] S1. The surface of the glass substrate was ultrasonically cleaned with ethanol at 20kHz for 10 minutes, and then ultrasonically cleaned with deionized water for 5 minutes. After the surface of the glass substrate was air-dried, it was placed in a plasma cleaner and continued to be cleaned for 10 minutes using oxygen to generate plasma. After cleaning, the surface was air-dried. The wurtzite boron nitride particles prepared in Preparation Example 3 were spread on the surface of the glass substrate, and 20g of wurtzite boron nitride particles were dispersed per square meter of the glass substrate surface. The surface of the wurtzite boron nitride particles was loaded with a steel plate and rubbed flat for 60s under a pressure of 2kg. Then, the wurtzite boron nitride particles on the surface of the glass substrate were removed by water spraying. After the surface was cleaned, the surface was dried. Then, silicon dioxide with a purity of 99.99% was used at a bottom pressure of 1.63×10 -1 sputtering and depositing a silicon oxide film under the conditions of 1:1.18, 24°C, pure argon, 44 sccm argon flow rate, and a ratio of argon to oxygen, wherein the average thickness of the silicon oxide film is 10 nm, to obtain a deposited glass;
[0055] S2. Take 1kg of copper, 0.01kg of rare earth lanthanum and 0.15kg of antimony oxide and mix them evenly. The purity of copper, rare earth lanthanum and antimony oxide is 99.99%. Under the protection of argon, heat them to 1200℃ and melt them completely. Then, under the protection of argon, spray them evenly onto the surface of the deposition glass. Then, anneal them. First, cool them to 690℃ at a cooling rate of 3℃ / min, then cool them to 550℃ at a cooling rate of 5℃ / min, and finally cool them to 250℃ at a cooling rate of 10℃ / min. The average thickness of the deposited film layer of copper, rare earth lanthanum and antimony oxide is 6nm. Purge with a nickel gun for 20min to obtain a semi-finished product. The semi-finished product is etched using nano-silicon dioxide particles as a mask. The average particle size of the nano-silicon dioxide particles is 40nm. The average etching depth of nano dry etching is 4nm to obtain a finished product.
[0056] Embodiment 4: This embodiment differs from Embodiment 1 in that:
[0057] No polycarbonate was added to the wurtzite boron nitride particles during the surface grinding process.
[0058] Embodiment 5: This embodiment differs from Embodiment 1 in that:
[0059] During the surface grinding process, rub for 5 minutes.
[0060] Embodiment 6: This embodiment differs from Embodiment 1 in that:
[0061] During the surface polishing process, wurtzite boron nitride particles are replaced with boron nitride whiskers of equal mass. The boron nitride whiskers are in the shape of long strips with an average length of 5 μm.
[0062] Embodiment 7: This embodiment differs from Embodiment 1 in that:
[0063] During the S2 metallic copper melt deposition process, no rare earth lanthanum and antimony oxide were added.
[0064] Embodiment 8: This embodiment differs from Embodiment 1 in that:
[0065] During the S2 copper metal melt deposition process, no antimony oxide was added.
[0066] Embodiment 9: This embodiment differs from Embodiment 1 in that:
[0067] During the S2 metal copper melt deposition process, the temperature was lowered to 200°C at a rate of 10°C / min during annealing. Comparative Example
[0068] Comparative Example 1: The difference between this preparation example and Example 1 is that:
[0069] S1 is not polished.
[0070] Comparative Example 2: The difference between this preparation example and Example 1 is that:
[0071] In S1, no silicon oxide film is sputter-deposited.
[0072] Comparative Example 3: The difference between this preparation example and Example 1 is that:
[0073] No metal melt deposition was performed in S2.
[0074] Comparative Example 4: The difference between this preparation example and Example 1 is that:
[0075] No nano dry etching was performed in S2.
[0076] Performance testing
[0077] 1. Contact angle detection
[0078] Optical films were prepared using the methods of Examples 1-3 and Comparative Example 2, respectively, and the contact angles were measured and the data were recorded.
[0079] 2. Reflectivity detection
[0080] Optical films were prepared by the methods of Examples 1-9 and Comparative Examples 1-4, and the reflectivity was measured at an oblique incident angle of 20° and 70° at a wavelength of 540 nm using a reflectivity detector. Five average values were taken and the data were recorded.
[0081] 3. Transmittance detection
[0082] Optical films were prepared by the methods of Examples 1-9 and Comparative Examples 1-4, and transmittance was measured at an oblique incident angle of 20° and 70° at a wavelength of 540 nm using a transmittance detector. Five average values were taken and the data were recorded.
[0083] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data)
[0084]
[0085] It can be seen from Examples 1-3 and Table 1 that the optical film prepared in the present application has a low reflectivity, a high transmittance, and a large contact angle, indicating a good hydrophobic effect.
[0086] It can be seen from Example 1 and Examples 4-9 and Table 1 that no polycarbonate was added to the wurtzite boron nitride particles during the surface grinding process of Example 4. Compared with Example 1, the reflectivity of the optical film prepared in Example 4 is higher than that of Example 1, and the transmittance is lower than that of Example 1; this illustrates the high toughness effect of the polycarbonate liquid, which ensures that the nanoscale scratches present an intermittent structure, and that long, excessive scratches are not prone to appear, and that the depth of scratches on the surface of the glass substrate during the flat grinding process is at the nanometer level, thereby ensuring that the optical film has the advantages of high transmittance and low reflectivity.
[0087] During the surface polishing process of Example 5, the surface was rubbed for 5 minutes. Compared with Example 1, the reflectivity of the optical film prepared in Example 5 was higher than that of Example 1, and the transmittance was lower than that of Example 1. This indicates that as the rubbing time is prolonged, scratches that are too long, too large, and too deep are more likely to appear, thereby affecting the low-reflection effect of the optical film under different wavelength conditions.
[0088] In the surface polishing process of Example 6, boron nitride whiskers of equal mass are used to replace wurtzite boron nitride particles. The boron nitride whiskers are in the shape of long strips. Compared with Example 1, the reflectivity of the optical film prepared in Example 6 is higher than that in Example 1, and the transmittance is lower than that in Example 1. This indicates that the long boron nitride whiskers can easily cause deep and long scratches on the surface during the grinding process, thereby easily affecting the low reflection and high transmittance effects of the optical film at different wavelengths.
[0089] In the process of melt deposition of metallic copper in Example 7, rare earth lanthanum and antimony oxide were not added. Compared with Example 1, the reflectivity of the optical film prepared in Example 7 was higher than that in Example 1, and the transmittance was lower than that in Example 1. This indicates that the combination of rare earth lanthanum and antimony oxide can alleviate the shrinkage of copper during annealing and ensure the uniformity of the film layer. The low reflection effect of rare earth lanthanum and antimony oxide can further improve the transmittance of the optical film and reduce the reflectivity.
[0090] In the process of melt deposition of metallic copper in Example 8, no antimony oxide was added. In the process of melt deposition of metallic copper in Example 9, the temperature was lowered to 200°C at a rate of 10°C / min during annealing. Compared with Example 1, the reflectivity of the optical films prepared in Examples 8 and 9 was higher than that in Example 1, and the transmittance was lower than that in Example 1. This indicates that during the annealing process, copper and rare earth lanthanum are first deposited and attached, and the viscosity and fluidity of the hot melt antimony oxide are used to pull copper and rare earth lanthanum, thereby preventing copper and rare earth lanthanum from agglomerating, shrinking and deforming, thereby affecting the uniformity of the nanofilm layer. The highly uniform nanofilm layer can further reduce the reflectivity of light of different wavelengths.
[0091] Combining Example 1 and Comparative Examples 1-4 and Table 1, it can be seen that Comparative Example 1 has not been polished, Comparative Example 2 has not been sputtered to deposit silicon oxide film, Comparative Example 3 has not been subjected to metal melt deposition, and Comparative Example 4 has not been subjected to nano-dry etching. Compared with Example 1, the optical film prepared in Comparative Examples 1, 2, 3, and 4 has a higher reflectivity than Example 1, and a lower transmittance than Example 1; this indicates that a silicon oxide film and a copper film are deposited on the surface of the glass substrate, and a refractive index gradient layer can be formed by introducing micro-nano structures with different refractive indices on the surface of the optical film, thereby further reducing the reflection of light at the interface; and nano-dry etching is performed to further adjust the nanoscale structure distribution. For incident light of different wavelengths, the micro-nano structure can reduce the reflection phenomenon caused by the sharp change in the refractive index, thereby making the incident light of different wavelengths have the advantage of low reflectivity; at the same time, the silicon oxide film, the copper film and the micro-nano structure can increase the contact angle, thereby improving the super-hydrophobic effect.
[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a super-hydrophobic optical film applicable to different wavelengths, characterized in that: The steps include: S1, after cleaning the surface of the glass substrate, performing surface polishing, after the surface is cleaned, sputtering and depositing a silicon oxide film to obtain a deposited glass; the surface polishing is performed by rubbing a plane with wurtzite boron nitride particles for 30-60 seconds, and the wurtzite boron nitride particles are prepared from a wurtzite boron nitride and polycarbonate liquid group with a mass ratio of 1:0.2-0.4; S2. Evenly mix copper with a purity of 99.99%, rare earth lanthanum and antimony oxide, wherein the raw material ratio of copper, rare earth lanthanum and antimony oxide is 1:0.005-0.01:0.01-0.015, and heat to 1100-1200° C. under argon protection until melted, and then spray onto the surface of the deposition glass under argon protection, and then anneal and blow with a nickel gun to obtain a semi-finished product; finally, perform nano dry etching to obtain a finished product.
2. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 1, characterized in that: The specific steps of cleaning in S1 are as follows: The glass substrate is ultrasonically cleaned by using one or more of acetone, ethanol and deionized water, and then cleaned by oxygen plasma.
3. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 1, characterized in that: The specific steps of sputtering and depositing the silicon oxide film are as follows: Using 99.99% pure silicon dioxide, at a base pressure of 1.58×10 -1 Pa-1.63×10 -1 Pa, temperature 24-27°C, pure argon, argon flow rate 42sccm-44sccm, the ratio of argon to oxygen is 1:1.12-1.
18.
4. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 1, characterized in that: The thickness of the deposited film layers of copper, rare earth lanthanum and antimony oxide is 4-6 nm.
5. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 1, characterized in that: The specific steps of the S2 annealing treatment are as follows: First, the temperature is lowered to 660-690°C at a cooling rate of 2-3°C / min, then to 510-550°C at a cooling rate of 3-5°C / min, and finally to 200-250°C at a cooling rate of 5-10°C / min.
6. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 1, characterized in that: The nickel gun is purged for 10-20 minutes.
7. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 1, characterized in that: The nanometer dry etching uses nanometer silicon dioxide particles as a mask for etching.
8. The method for preparing a super-hydrophobic optical film applicable to different wavelengths according to claim 7, characterized in that: The average etching depth of the semi-finished product surface is 3-4 nm.
Citation Information
Patent Citations
Preparation method and application of monocrystal diamond nano-pillar array structure
CN104724664A
Superhydrophobic and superoleophobic nanosurfaces
US20140011013A1